00 upvotes00 downvotes

9 views7 pagesFormulas

Oct 30, 2016

© © All Rights Reserved

DOCX, PDF, TXT or read online from Scribd

Formulas

© All Rights Reserved

9 views

00 upvotes00 downvotes

Formulas

© All Rights Reserved

You are on page 1of 7

(ii) If a is rational, b is a surd and a + b (or, a - b) = 0 then a = 0 and b = 0.

(iii) If a and x are rational, b and y are surds and a + b = x + y then a = x and b = y.

Complex Numbers:

(i) The symbol z = (x, y) = x + iy where x, y are real and i = -1, is called a complex (or,

imaginary) quantity;x is called the real part and y, the imaginary part of the complex number z =

x + iy.

(ii) If z = x + iy then z = x - iy and conversely; here, z is the complex conjugate of z.

(iii) If z = x+ iy then

(a) mod. z (or, | z | or, | x + iy | ) = + (x + y) and

(b) amp. z (or, arg. z) = = tan1

y/x (- < ).

(iv) The modulus - amplitude form of a complex quantity z is

z = r (cos + i sin); here, r = | z | and = arg. z (- < <= ).

(v) | z | = | -z | = z z = (x + y).

(vi) If x + iy= 0 then x = 0 and y = 0(x,y are real).

(vii) If x + iy = p + iq then x = p and y = q(x, y, p and q all are real).

(viii) i = -1, i = -1, i = -i, and i = 1.

(ix) | z + z| | z | + | z |.

(x) | z z | = | z | | z |.

(xi) | z/z| = | z |/| z |.

(xii) (a) arg. (z z) = arg. z + arg. z + m

(xiii) If be the imaginary cube root of unity then = (- 1 + 3i) or, = (-1 - 3i)

(xiv) = 1 and 1 + + = 0

Variation:

(i) If x varies directly as y, we write x y or, x = ky where k is a constant of variation.

(ii) If x varies inversely as y, we write x 1/y or, x = m (1/y) where m is a constant of variation.

(iii) If x y when z is constant and x z when y is constant then x yz when both y and z vary.

(i) The general form of an A. P. is a, a + d, a + 2d, a + 3d,.....

where a is the first term and d, the common difference of the A.P.

(ii) The nth term of the above A.P. is t = a + (n - 1)d.

(iii) The sum of first n terns of the above A.P. is s = n/2 (a + l) = (No. of terms/2)[1st term + last

term] or, S = / [2a + (n - 1) d]

(iv) The arithmetic mean between two given numbers a and b is (a + b)/2.

(v) 1 + 2 + 3 + ...... + n = [n(n + 1)]/2.

(vi) 1 + 2 + 3 +. + n = [n(n+ 1)(2n+ 1)]/6.

(vii) 1 + 2 + 3 + . . . . + n = [{n(n + 1)}/2 ].

(i) The general form of a G.P. is a, ar, ar, ar, . . . . . where a is the first term and r, the common

ratio of the G.P.

(ii) The n th term of the above G.P. is t = a.rn1

.

(iii) The sum of first n terms of the above G.P. is S = a [(1 - r)/(1 r)] when -1 < r < 1

or, S = a [(r 1)/(r 1) ]when r > 1 or r < -1.

(iv) The geometric mean of two positive numbers a and b is (ab) or, -(ab).

(v) a + ar + ar + . = a/(1 r) where (-1 < r < 1).

ax + bx + c = 0 ... (1)

(i) Roots of the equation (1) are x = {-b (b 4ac)}/2a.

(ii) If and be the roots of the equation (1) then,

sum of its roots = + = - b/a = - (coefficient of x)/(coefficient of x );

and product of its roots = = c/a = (Constant term /(Coefficient of x).

(iii) The quadratic equation whose roots are and is

x - ( + )x + = 0

i.e. , x - (sum of the roots) x + product of the roots = 0.

(iv) The expression (b - 4ac) is called the discriminant of equation (1).

(v) If a, b, c are real and rational then the roots of equation (1) are

(a) real and distinct when b - 4ac > 0;

(b) real and equal when b - 4ac = 0;

(c) imaginary when b - 4ac < 0;

(e) irrational when b - 4ac is not a perfect square.

(vi) If + i be one root of equation (1) then its other root will be conjugate complex quantity i and conversely (a, b, c are real).

(vii) If + be one root of equation (1) then its other root will be conjugate irrational quantity

- (a, b, c are rational).

Permutation:

(i) n (or, n!) = n (n 1) (n 2) 321.

(ii) 0! = 1.

(iii) Number of permutations of n different things taken r ( n) at a time P = n!/(n - 1)! = n (n

1)(n - 2) (n - r + 1).

(iv) Number of permutations of n different things taken all at a time = P = n!.

(v) Number of permutations of n things taken all at a time in which p things are alike of a first

kind, q things are alike of a second kind, r things are alike of a third kind and the rest are all

different, is <span style='font-size: 50%'>!/

(vi) Number of permutations of n different things taken r at a time when each thing may be

repeated upto r times in any permutation, is n .

Combination:

(i) Number of combinations of n different things taken r at a time = Cr = n!r!(nr)!

(ii) P = r! C.

(iii) C = Cn = 1.

(iv) Cr = Cn - r.

(v) Cr + Cn - 1 = n+1Cr

(vii) Cr/Cr - 1 = (n - r + 1)/r.

(viii) The total number of combinations of n different things taken any number at a time = C +

C + C + . + C = 2 1.

(ix) The total number of combinations of (p + q + r + . . . .) things of which p things are alike of a

first kind, q things are alike of a second kind r things are alike of a third kind and so on, taken

any number at a time is [(p + 1) (q + 1) (r + 1) . . . . ] - 1.

Binomial Theorem:

(i) Statement of Binomial Theorem : If n is a positive integer then

(a + x)n = an + nC1 an - 1 x + nC2 an - 2 x2 + .. + nCr an - r xr + .. + xn .. (1)

(ii) If n is not a positive integer then

(1 + x)n = 1 + nx + [n(n - 1)/2!] x2 + [n(n - 1)(n - 2)/3!] x3 + + [{n(n-1)(n-2)..

(n-r+1)}/r!] xr+ . (-1 < x < 1) .(2)

(iii) The general term of the expansion (1) is (r+ 1)th term

= tr + 1 = nCr an - r xr

(iv) The general term of the expansion (2) is (r + 1) th term

= tr + 1 = [{n(n - 1)(n - 2)....(n - r + l)}/r!] xr.

(v) There is one middle term is the expansion ( 1 ) when n is even and it is (n/2 + 1)th term ; the

expansion ( I ) will have two middle terms when n is odd and they are the {(n - 1)/2 + 1} th and

{(n - 1)/2 + 1} th terms.

(vi) (1 - x)-1 = 1 + x + x2 + x3 + ..

(vii) (1 + x)-1 = I - x + x2 - x3 + .

(viii) (1 - x)-2 = 1 + 2x + 3x2 + 4x3 + . . . . .

Logarithm:

(i) If ax = M then loga M = x and conversely.

(ii) loga 1 = 0.

(iii) loga a = 1.

(iv) a logam = M.

(v) loga MN = loga M + loga N.

(vi) loga (M/N) = loga M - loga N.

(vii) loga Mn = n loga M.

(viii) loga M = logb M x loga b.

(ix) logb a x 1oga b = 1.

(x) logb a = 1/logb a.

(xi) logb M = logb M/loga b.

Exponential Series:

(i) For all x, ex = 1 + x/1! + x2/2! + x3/3! + + xr/r! + .. .

(ii) e = 1 + 1/1! + 1/2! + 1/3! + .. .

(iii) 2 < e < 3; e = 2.718282 (correct to six decimal places).

(iv) ax = 1 + (loge a) x + [(loge a)2/2!] x2 + [(loge a)3/3!] x3 + .. .

Logarithmic Series:

(ii) loge (1 - x) = - x - x2/ 2 - x3/3 - .. (- 1 x < 1).

(iii) loge [(1 + x)/(1 - x)] = x + x3/3 + x5/5 + (-1 < x < 1).

(iv) loge 2 = 1 - 1/2 + 1/3 - 1/4 + .

(v) log10 m = loge m where = 1/loge 10 = 0.4342945 and m is a positive number.

## Much more than documents.

Discover everything Scribd has to offer, including books and audiobooks from major publishers.

Cancel anytime.